2010
DOI: 10.1177/1741143209359714
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Curriculum Leadership in Action: A Hong Kong Case Study

Abstract: This study was designed primarily to investigate the impact of school-based curriculum development teams on teacher development within the tradition of school-based curriculum development. The results are expected to provide valuable insights for teachers, school management and policy making. Teacher interviews in a primary school in Hong Kong were conducted to evaluate the extent to which teacher engagement in curriculum decision-making processes, which are within two school-based curriculum development teams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…Fitzgerald and Gunter (2008) refer to the residual significance of authority and hierarchy, and note the 'dark side' of distributed leadership, managerialism in a new guise. It can also be argued that distributed leadership leads to the power relationship between followers and leaders becoming blurred (Law, Galton, and Wan 2010). Lumby (2013) also links distributed leadership to power, claiming that little attention is given to the implications of the former for power relations in education.…”
Section: Distributed Leadershipmentioning
confidence: 97%
“…Fitzgerald and Gunter (2008) refer to the residual significance of authority and hierarchy, and note the 'dark side' of distributed leadership, managerialism in a new guise. It can also be argued that distributed leadership leads to the power relationship between followers and leaders becoming blurred (Law, Galton, and Wan 2010). Lumby (2013) also links distributed leadership to power, claiming that little attention is given to the implications of the former for power relations in education.…”
Section: Distributed Leadershipmentioning
confidence: 97%
“…M. Cheung & Walker, 2006;Chui et al, 1996;Dimmock & Walker, 2005;Ho, 2010;Ho & Tikly, 2012;E. H. F. Law, 2011;E. Law et al, 2010;L.…”
Section: Emergent Findingsmentioning
confidence: 95%
“…These studies have focused on principals (e.g., Chui, Sharpe, & McCormick, 1996 Wong, 2011;Yu, Leithwood, & Jantzi, 2002), vice principals (e.g., Kwan, 2009aKwan, , 2009b; J. C. K. Lee, Kwan, & Walker, 2009), middle-level managers (e.g., department heads, curriculum leaders), and teacher leaders (e.g., Ho, 2010;Ho & Tikly, 2012;E. Law et al, 2010;M.…”
Section: Topical Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially so in educational systems which are becoming more decentralized. A study from Hong Kong has shown how curriculum innovation has occurred through distributed leadership (Law et al 2010). When teachers were given autonomy and a greater responsibility of developing new curricular, the resultant ownership greatly enhanced the innovation's success (Kennedy 2010;Law et al 2010).…”
Section: Discussion and Deliberationsmentioning
confidence: 98%